REFORMULASI HUKUM ISLAM DALAM KONTEKS MULTIKULTURALIS-PLURALITAS DI INDONESIA - Rahmawati, Rahmawati (DIKTUM: Jurnal Syariah dan Hukum, 2013)
This paper examines refomulasi Islamic law in the middle of the plurality of phenomena both in terms of culture and religion in Indonesia. Beginning with a discussion of basic concepts of multiculturalism and pluralism of society and a general overview of the phenomenon of plurality (plurality) in Indonesian society. From these discussions then analyzed how to reformulate the application of Islamic law in the context of multicultural-plurality in Indonesia. Based on this analysis, it was concluded that the application of Islamic law in the context of the Indonesian national diversity leads to a cultural approach, which emphasizes the principles and values that are universal Islamic teachings such as fairness, honesty, freedom under the law, the legal protection of the public is not the same religion, and upholding the rule of God's law. While the application through the formalization of Islamic law in the national legal system is still limited to the civil rules.